The Tindalos asset - Kiernan, Caitlín R. (Kiernan, Caitlín R. Tinfoil dossier, 2020)
"A rundown apartment in Koreatown. A Los Angeles winter. A strung out, worn out, wrecked and used government agent is scraped up off the pavement, cleaned up, and reluctantly sent out into battle one last time. Ellison Nicodemo has seen and done terrible things. She thought her only remaining quest was for oblivion. Then the Signalman comes calling. He wants to learn if she can stop the latest apocalypse. Ellison, once a unique and valuable asset, can barely remember why she ever fought the good fight. Still, you don't say no to the Signalman, and the time has come to face her fears and the nightmare forces that almost destroyed her. Only Ellison can unleash the hound of Tindalos. . ."--Provided by publisher.